ORGANIZATIONAL MANAGEMENT: NEW ASPECTS IN THE FIELD OF SMALL BUSINESS MANAGEMENT (Development Service Industry Management, 2025)
The study acknowledges that economic sustainability within an enterprise represents a dynamic and complex construct, defined as the organization's capacity to adapt to external environmental fluctuations while efficiently utilizing internal resources to maintain operational stability and foster long-term development. The research demonstrates that the core elements of economic resilience encompass both internal (financial, human, and material resources) and external (macro-environmental influences) factors, which must be strategically integrated to ensure the enterprise’s viability under conditions of uncertainty and risk.A well-structured economic sustainability management system is identified as a critical mechanism for maintaining organizational stability amid continuous environmental volatility. It is emphasized that economic sustainability should not be perceived as a static condition but rather as an ongoing, adaptive process necessitating regular review and responsiveness to changing circumstances.The foundational principles guiding such a system include comprehensiveness, adaptability, pragmatism, and efficiency, which collectively mandate the consideration of all relevant internal and external determinants. The enterprise’s ability to promptly respond to market dynamics and flexibly recalibrate its strategic trajectory is highlighted as a key factor of resilience. Furthermore, the management system’s primary functions include continuous financial monitoring, the anticipation of potential threats, and the formulation of robust instruments to sustain enterprise stability.The application of a systems-based approach, combined with adaptive management techniques, significantly enhances the potential to achieve higher levels of economic resilience in turbulent business environments. Evaluating the economic sustainability status of an enterprise is a pivotal managerial function, as it facilitates the identification of existing vulnerabilities and the assessment of actual prospects for advancement.In this context, the study synthesizes current and relevant insights while proposing targeted strategies for managing the economic sustainability of small and medium-sized enterprises (SMEs), particularly under wartime conditions. Consequently, it advocates for the governance of economic sustainability to be grounded in the principles of systematicity, adaptability, integrality, continuity, economic rationality, optimality, alignment with environmental conditions, and strategic foresight.
Keywords: economic sustainability management; assessment of the level of economic sustainability; methodological approaches to determining economic sustainability; principles of economic sustainability management; mechanism for managing the economic sustainability of small and medium-sized businesses